Meaningful use of a digital platform and structured telephone support to facilitate remote person-centred care - a mixed-method study on patient perspectives - Emmelie Barenfeld; Joanne M. Fuller; Sara Wallström; Andreas Fors; Lilas Ali; Inger Ekman (BMC, 2022)
Abstract Background Process evaluations are useful in clarifying results obtained from randomised controlled trials (RCTs). Traditionally, the degree of intervention usage in process evaluations is monitored by measuring dose or evaluating implementation fidelity. From a person-centred perspective, such evaluations should be supplemented with patients' experiences of meaningful use, given that intervention use should be agreed upon between interested parties and tailored to each patient. This study aimed to elucidate patients' experiences of a remote person-centred care (PCC) intervention by deepening the understanding of, if, how and for whom the intervention contributed to meaningful use. Methods Patients (n = 86) were recruited from the RCT PROTECT intervention group. A convergent mixed-method approach was implemented. Data were collected in parallel with the ongoing RCT via a survey, including ratings and written comments on meaningful or non-meaningful use. Also, interviews were performed with twelve purposefully selected participants. Descriptive statistics, logistic regression and content analysis were employed. Data sources were integrated in the results. Results Most participants rated the overall intervention as meaningful to use, with the telephone support rated as most meaningful. Interviews and written comments showed that patient ratings on meaningful use were explained by four categories: Not in need, Communication deficiency, Benefits in everyday life and A personal boost. Meaningful use of rating symptoms on the digital platform was predicted by living alone (adjusted odds ratio [aOR] = 2.8 P = .044). A diagnosis of chronic obstructive pulmonary disease (COPD) predicted meaningful use of digital platform direct messaging (aOR = 3.5, P = .045). Moreover, having access to direct-dial telephone contact explained meaningful use among participants with low ratings of technical competence (aOR = 3.6, P = .014). Conclusions The combined digital platform and structured telephone support could be helpful in identifying preventive actions to maintain health for people diagnosed with COPD and chronic heart failure but tends to be more meaningful for those diagnosed with COPD. Overall, lower adoption of the digital platform was seen compared to telephone support. Shortcomings were noted in the digital platform's implementation that negatively influences experiences of meaningful use. When used, the intervention proved to be an easily applicable and valued tool to support preventive actions in a person-centred manner.